2010
DOI: 10.1111/j.1365-2141.2010.08429.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary ocular adnexal mucosa‐associated lymphoid tissue lymphoma (MALT): single institution experience in a large cohort of patients

Abstract: SummaryExtranodal marginal zone B-cell lymphoma is the most common orbital tumour. We conducted a retrospective analysis to examine: (i) the impact of initial presentation and staging on outcome and (ii) response to various treatment modalities and the effect of the latter on recurrence. Ninety patients with primary ocular adnexal marginal zone lymphoma (POAML) diagnosed at our institution between 1984 and 2009 were studied. POAML was associated with monoclonal gammopathy (13%) at presentation. Most POAML pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 64 publications
5
51
0
1
Order By: Relevance
“…Twenty peer-reviewed articles were reviewed from 1997 to 2013 [4,8,12,14,15,16,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. All patients treated with radiation therapy only were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty peer-reviewed articles were reviewed from 1997 to 2013 [4,8,12,14,15,16,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. All patients treated with radiation therapy only were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…However, an association between POAML and C psittaci was reported in other geographic regions. 8,9 Consequently, doxycycline treatment was studied as an initial therapeutic approach to POAML in several studies. [37][38][39] The overall response rate ranges from 45% to 65% in most studies 37,40 but was zero in a study reported by Grunberger et al 41 The 5-year For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Multiple retrospective studies have described clinical and epidemiological features of primary ocular adnexal MALT lymphoma (POAML), including female preponderance, frequent occurrence in the orbit, and increased incidence of bilateral involvement. 8 Association with Chlamydia psittaci infection in certain geographic areas has also been reported. 9 The pathogenesis of these tumors was elucidated by an investigation of the prevalence of chromosomal translocations and mutations, which showed alterations in genes that regulate cell survival and apoptosis pathways, as well as through interrogation of immunoglobulin gene usage and analysis of somatic mutations.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations